2014
DOI: 10.1111/jop.12263
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of bone remodeling molecules expression in different types of jaw ameloblastoma

Abstract: Our results suggest OPG overexpression and RANKL underexpression in solid ameloblastoma; this may reflect a possible prevalence of the OPG/TRAIL over the OPG/RANKL signaling pathway, resulting in inactivation of TRAIL-induced apoptosis in ameloblastic cells. In unicystic ameloblastoma, the RANKL/OPG expression immunoprofile among histological variants is compatible with the reported biologic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies of AM have demonstrated that many molecular processes are involved in tumor progression. These processes include proteins involved in cell adhesion [ 23 ], bony reconstruction, tumor front [ 24 , 25 ], apoptosis regulation, cell cycle/cell proliferation [ 2 , 26 , 27 ], and epidermal growth factor gene and BRAF V600 E mutations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of AM have demonstrated that many molecular processes are involved in tumor progression. These processes include proteins involved in cell adhesion [ 23 ], bony reconstruction, tumor front [ 24 , 25 ], apoptosis regulation, cell cycle/cell proliferation [ 2 , 26 , 27 ], and epidermal growth factor gene and BRAF V600 E mutations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical study of proteins associated with the cell cycle helps in the understanding of the biological behavior of certain neoplasms. 5 Growth and tumoral progression of ameloblastomas are related to diverse molecular processes, such as adhesion, 23 invasion, 24 growth factors, 25 apoptosis, 26 and cell proliferation, 19 among others.…”
Section: Discussionmentioning
confidence: 99%
“…From the nine studies analyzed, only three (14,21,22) mentioned the ethical criteria involved. As for specimen fixation, five studies (13,14,21,23,25) used 10% formaldehyde and four studies (4,22,24,26) did not mention the means of fixation. All studies (4,13,14,21-26) used immunohistochemistry as the diagnostic method.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four studies (13,14,22,23) used anti-OPG (N-20; Santa Cruz Biotechnology) and anti-RANKL (N-19; Santa Cruz Biotechnology) primary polyclonal antibodies from rabbits, while two studies (21,25) used anti-OPG (H-249, scll383, Santa Cruz Biotechnology) and anti-RANKL (FL-327, sc9073, Santa Cruz Biotechnology) primary polyclonal antibodies from rabbits. One study (24) used anti-OPG (clone ab73400 Abcam laboratories), anti-RANK (clone 64C1385 Abcam laboratories), and anti-RANKL (clone 12A668 Abcam laboratories) antibodies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation